Epic imege tradition In A. Kadiri "Lastr days" - soatova, nodira (FILOLOGIYA UFQLARI JURNALI, 2022)
This monograph is devoted to the study of folklore and epic traditions of Alisher Navoi in the monograph of Abdullah Kadiri 's novel "Last Days"(Bygone days). In this regard, this work is intended for those who aim for an in-depth study of the interrelationships of oral and written literature, literary tradition and innovation, writing skills, and contemporary topics